INDIVIDUAL BEHAVIOUR FORMED BY ISLAMIC EDUCATIONAL INSTITUTIONS IN INDONESIA: ANALYSIS-DESCRIPTIVE STUDY - Muzakki, Hawwin; Natsir, Ahmad; Nuha, Muhammad Afthon Ulin (IAIN PONOROGO, 2023)
This research will examine how organizational institutions influence the formation of individual behaviour, while many other studies emphasize how individual behaviour influences organizational culture. This research will provide a broader picture of the factors that influence the formation of individual behaviour, especially from the perspective of organizational institutions. The method used in this research is a literature study, which collects data through written sources such as relevant journals and books. Data analysis was done using descriptive analysis, looking for patterns and finding themes from the collected materials. This study concludes (1) Islamic educational institutions in Indonesia can shape the biographical character of moderate Indonesian Islam, (2) Islamic educational institutions in Indonesia seek to shape individual behaviour that has the expected abilities following Islamic teachings and principles, (3) Islamic educational institutions in Indonesia strive to form positive personalities, namely individuals who have integrity, professionalism, innovation, responsibility and exemplary. (4) The process of behaviour change that occurs in Islamic educational institutions in Indonesia can occur through social interaction, understanding of Islamic teachings, and the relationship between individual behaviour and the consequences it produces. Penelitian ini akan mengkaji bagaimana institusi organisasi mempengaruhi pembentukan perilaku individu, sementara banyak penelitian lain yang menekankan bagaimana perilaku individu mempengaruhi budaya organisasi. Penelitian ini akan memberikan gambaran yang lebih luas mengenai faktor-faktor yang mempengaruhi pembentukan perilaku individu, terutama dari sudut pandang institusi organisasi. Metode yang digunakan dalam penelitian ini adalah studi literatur, yaitu pengumpulan data melalui sumber tertulis seperti jurnal dan buku yang relevan. Analisis data dilakukan dengan menggunakan analisis deskriptif, mencari pola dan menemukan tema dari bahan yang dikumpulkan. Penelitian ini menyimpulkan (1) Lembaga pendidikan Islam di Indonesia dapat membentuk karakter biografi Islam Indonesia yang moderat, (2) Lembaga pendidikan Islam di Indonesia berupaya membentuk perilaku individu yang memiliki kemampuan yang diharapkan sesuai dengan ajaran dan prinsip Islam, (3) Pendidikan Islam institusi di Indonesia berupaya untuk membentuk pribadi-pribadi positif, yaitu individu-individu yang mempunyai integritas, profesionalisme, inovasi, tanggung jawab dan keteladanan. (4) Proses perubahan perilaku yang terjadi pada lembaga pendidikan Islam di Indonesia dapat terjadi melalui interaksi sosial, pemahaman ajaran Islam, dan hubungan antara perilaku individu dengan akibat yang ditimbulkannya.